Hitler's theology: A cautionary tale for today's peril. Issue 1 (3rd February 2021) - Hinlicky, Paul R.
Abstract: In this article the author updates and renews his thesis from 2013 about the Weimarization of American political culture. He argues that fascism is an endemic modern possibility that has a theological dimension that becomes visible when the left‐right ideological binary descending from the French Revolution is set aside. Reviewing the evidence from Hitler's Table Talks, he shows how Hitler both understood himself as a progressive change agent and envisioned writing a new theology for triumphant Nazism in retirement. The article concludes by drawing upon Giorgio Agamben's analysis of Nazi biopolitics in Homo Sacer to point towards a messianic alternative.